Estimating the Global Prevalence, Disease Progression, and Clinical Outcome of Hepatitis Delta Virus Infection - Miao, Zhijiang; Zhang, Shaoshi; Ou, Xumin; Li, Shan; Ma, Zhongren; Wang, Wenshi; Peppelenbosch, Maikel P; Liu, Jiaye; Pan, Qiuwei (The Journal of infectious diseases, 2020)
Abstract Background Hepatitis delta virus (HDV) coinfects with hepatitis B virus (HBV) causing the most severe form of viral hepatitis. However, its exact global disease burden remains largely obscure. We aim to establish the global epidemiology, infection mode-stratified disease progression, and clinical outcome of HDV infection. Methods We conducted a meta-analysis with a random-effects model and performed data synthesis. Results The pooled prevalence of HDV is 0.80% (95% confidence interval [CI], 0.63–1.00) among the general population and 13.02% (95% CI, 11.96–14.11) among HBV carriers, corresponding to 48–60 million infections globally. Among HBV patients with fulminant hepatitis, cirrhosis, or hepatocellular carcinoma, HDV prevalence is 26.75% (95% CI, 19.84–34.29), 25.77% (95% CI, 20.62–31.27), and 19.80% (95% CI, 10.97–30.45), respectively. The odds ratio (OR) of HDV infection among HBV patients with chronic liver disease compared with asymptomatic controls is 4.55 (95% CI, 3.65–5.67). Hepatitis delta virus-coinfected patients are more likely to develop cirrhosis than HBV-monoinfected patients with OR of 3.84 (95% CI, 1.79–8.24). Overall, HDV infection progresses to cirrhosis within 5 years and to hepatocellular carcinoma within 10 years, on average. Conclusions Findings suggest that HDV poses a heavy global burden with rapid progression to severe liver diseases, urging effective strategies for screening, prevention, and treatment. Forty-eight to 60 million individuals are infected with HDV around the globe, and Asia and Africa are the worst-hit areas. HDV infection predisposes to rapid progression into severe liver diseases, particularly liver cirrhosis.